In Search of the jüdische Typus: A Proposed Benchmark to Test the Genetic Basis of Jewishness Challenges Notions of “Jewish Biomarkers” - Elhaik, Eran (Frontiers in Genetics, 2016)
The debate as to whether Jewishness is a biological trait inherent from an “authentic” “Jewish type” (jüdische Typus) ancestor or a system of beliefs has been raging for over two centuries. While the accumulated biological and anthropological evidence support the latter argument, recent genetic findings, bolstered by the direct-to-consumer genetic industry, purport to identify Jews or quantify one’s Jewishness from genomic data. To test the merit of claims that Jews and non-Jews are genetically distinguishable, we propose a benchmark where genomic data of Jews and non-Jews are hybridized over two generations and the observed and predicted Jewishness of the terminal offspring according to either the Orthodox religious law (Halacha) or the Israeli Law of Return are compared. Members of academia, the public, and 23andMe were invited to use the benchmark to test claims that Jews are genetically distinct from non-Jews. Here, we report the findings from these trials. We also compare the genomic similarity of ∼300 individuals from nearly thirty Afro-Eurasian Jewish communities to a simulated jüdische Typus population. The results are discussed in light of modern trends in the genetics of Jews and related fields and provide a tentative answer to the ageless question “who is a Jew?”